2021
DOI: 10.3389/fmolb.2021.755911
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Pan-Cancer Analysis of PBK in Human Tumors

Abstract: Background: PDZ binding kinase (PBK) is a serine/threonine kinase, which belongs to the mitogen-activated protein kinase kinase (MAPKK) family. It has been shown to be a critical gene in the regulation of mitosis and tumorigenesis, but the role of PBK in various cancers remains unclear. In this study, we systematically explored the prognostic and predictive value of PBK expression in 33 cancer types.Methods: Public databases including the cBioPortal database, GDSC database, GTEx database, CCLE database, and TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies have also reported the overexpression of PBK in multiple cancer types, such as glioma, leukemia, colorectal, ovarian, skin and lung cancer (31,50). Targeting PBK with HI-TOPK-032 or other novel inhibitors, such as OTS514, OTS964 and ADA-07 in these cancer types has shown promising anticancer efficacy as well (31,35).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also reported the overexpression of PBK in multiple cancer types, such as glioma, leukemia, colorectal, ovarian, skin and lung cancer (31,50). Targeting PBK with HI-TOPK-032 or other novel inhibitors, such as OTS514, OTS964 and ADA-07 in these cancer types has shown promising anticancer efficacy as well (31,35).…”
Section: Discussionmentioning
confidence: 98%
“…As a mitotic kinase, PBK/TOPK is important for the proliferation, progression and metastasis of many cancers 23 . Wen et al confirmed that up‐regulation of PBK/TOPK has also been shown to be associated with cancer diagnosis and prognosis, and therefore, it may be a potential therapeutic target for a variety of malignancies 24 . Ohashi et al confirmed that overexpression of PBK/TOPK leads to tumor development and poor prognosis of ESCC 25 .…”
Section: Discussionmentioning
confidence: 98%
“…PBK is highly expressed in cancers such as breast, lung, and leukaemia and is associated with unfavourable prognostic outcomes[ 45 - 47 ]. In addition, PBK was identified as a potential target for a novel anti-SARS-CoV-2 agent[ 48 ], suggesting that PBK has a common potential targeting therapeutic value for cancer and COVID-19. TPX2 is a microtubule-associated protein whose expression is strictly regulated by the cell cycle and participates in cell cycle progression by maintaining the stability of the mitotic spindle[ 49 ].…”
Section: Discussionmentioning
confidence: 99%